Sosial Capital of Community Forest Management in Lombang Village Majene Regency - Arafat, Andi; Idris, Andi Irmayanti; Wijayanti, Andi Ridha Yayank (Pangale Journal of Forestry and Environment, 2021)
Community forest management cannot be separated from social/communal conditions. Emerging Natural Resource Management arises This occurs when there are interactions (regular and ongoing) between community members that are manifested in social capital such as social trust, social norms, and social networks that have a relationship with community welfare. The study was conducted in Lombang Village, Majene Regency, West Sulawesi Province. This is important for the development of social capital (norms, mutual trust, and social networks) that exist in forest management people. Then, look at the relationship and role of social capital in community forest development. The results of the study show that social capital in the forest owner / manager is referred to as a high category because the community has informal associations that are stronger and have collective values, norms and ethics as an interconnected community. Communities that have high social capital will be resolved. The existence of mutual trust, support, and collaboration they can build networks both within their community groups and with other community groups.